Impact of wearing a surgical and cloth mask during cycle exercise - Doherty, C. J.; Mann, L. M.; Angus, S. A.; Chan, J. S.; Molgat-Seon, Y.; Dominelli, P. B. (Applied Physiology, Nutrition, and Metabolism, 2021)
We sought to determine the impact of wearing cloth or surgical masks on the cardiopulmonary responses to moderate-intensity exercise. Twelve subjects (n = 5 females) completed three, 8-min cycling trials while breathing through a non-rebreathing valve (laboratory control), cloth, or surgical mask. Heart rate (HR), oxyhemoglobin saturation (SpO2), breathing frequency, mouth pressure, partial pressure of end-tidal carbon dioxide (PetCO2) and oxygen (PetO2), dyspnea were measured throughout exercise. A subset of n = 6 subjects completed an additional exercise bout without a mask (ecological control). There were no differences in breathing frequency, HR or SpO2 across conditions (all p > 0.05). Compared with the laboratory control (4.7 ± 0.9 cmH2O [mean ± SD]), mouth pressure swings were smaller with the surgical mask (0.9 ± 0.7; p < 0.0001), but similar with the cloth mask (3.6 ± 4.8 cmH2O; p = 0.66). Wearing a cloth mask decreased PetO2 (-3.5 ± 3.7 mm Hg) and increased PetCO2 (+2.0 ± 1.3 mm Hg) relative to the ecological control (both p < 0.05). There were no differences in end-tidal gases between mask conditions and laboratory control (both p > 0.05). Dyspnea was similar between the control conditions and the surgical mask (p > 0.05) but was greater with the cloth mask compared with laboratory (+0.9 ± 1.2) and ecological (+1.5 ± 1.3) control conditions (both p < 0.05). Wearing a mask during short-term moderate-intensity exercise may increase dyspnea but has minimal impact on the cardiopulmonary response. Novelty: • Wearing surgical or cloth masks during exercise has no impact on breathing frequency, tidal volume, oxygenation, and heart rate • However, there are some changes in inspired and expired gas fractions that are physiologically irrelevant. • In young healthy individuals, wearing surgical or cloth masks during submaximal exercise has few physiological consequences.